Analisis Persepsi Konsumen Terhadap Produk Kuliner Pindang Meranjat - Karo Karo, Pelliyezer (Politeknik Pariwisata Medan, 2024)
The research on consumer perception of Pindang Meranjat was conducted at the original location where this culinary product originated, namely Ogan Ilir Regency, South Sumatra Province. The study was conducted using a quantitative approach through four organoleptic variables, consisting of color, aroma, texture, and taste, on the three main parts of the pindang product, namely the side dish, broth, and condiments, with 12 indicators. Primary data were collected through questionnaires from 55 respondents, consisting of 49 consumers who repurchased Pindang and 6 experts. The method used is Importance Performance Analysis, which consists of the Suitability Index approach and mapping through a Cartesian diagram. The research results show that out of the four variables, the color variable is identified as the only variable that meets the average level of consumer perception and expectation; the aroma variable is the variable that does not meet both levels; and the other two variables, texture, and taste, only meet the expectation level. Furthermore, it was found that three indicators are the main priorities for improving the quality of the Pindang Meranjat product, in order of highest priority: improvement of the broth texture, broth taste, and the aroma of the side dish of the product in question. The next potential variable for improving quality is the improvement of the condiment texture. Through these results, it is hoped that they can serve as a basis for structured improvements so that the quality of the Pindang Meranjat product increases to meet consumer expectations as an authentic culinary product with the potential to become a culinary tourism attraction from Ogan Ilir Regency.